Parametric studies on tramcar suspension system - Mohamed Rehan, Muhammad Saifuddin; Yusof, Mustafa; Abd. Rahman, Roslan (2006)
Suspension system plays an important role in the performance of a vehicle, especially the handling and ride comfort. The role of suspension parameter, particularly spring stiffness, in relation to ride quality is being analysed in this paper. This study focused on the suspension system of a non-commercial transport for recreational purposes designed by the Mechanical Engineering Faculty of Universiti Teknologi Malaysia, which is commonly known as ‘tramcar’. For the purpose of the analysis, a full car model for the tramcar suspension system was developed. The simulation on the model was performed using MATLAB Simulink software. The spring stiffness value was varied in the simulation, and the suspension response was observed. From the suspension parameter analysis, it was concluded that the ride comfort of the tramcar can be improved to an optimum level by having the lowest practical spring stiffness value. Lower suspension spring stiffness was shown to provide better ride comfort in term of lower acceleration, pitch rate and roll rate responses. However, the spring stiffness should not produce response frequencies lower than 1Hz in avoiding sensations assimilated to motion sickness